Location decisions in pop-up retailing: Focus on the Finnish fashion sector - Polo, Annabella (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
This study examines location decisions in pop-up retailing in the Finnish fashion sector. In recent years, the temporary retailing format has quickly become a significant global phenomenon. Pop-up stores appeal to modern customers because they aim at offering unique brand experiences. Retail location is a critical element of pop-up retailing because it forms part of the retail experience and influences store performance. The identified research gap is twofold: academic literature on the pop-up retailing phenomenon remains narrow; and the research on location decisions focuses mainly on traditional and large-scale retailing. The following sub objectives function as the guideline of the study: what kind of retail locations are selected for pop-up stores, how are retail locations selected for pop-up stores, and what kind of location-related decisions are made in pop-up stores after the retail location has been selected? A theoretical framework is created by combining previous research on location decisions in traditional retailing environment with pop-up retailing research. This study is qualitative-explorative by nature. The empirical data was collected through seven expert interviews in the Finnish fashion sector. With an active participation in locational planning and decision-making in pop-up stores, the experts provide first-hand information of the phenomenon. The findings present preliminary understanding of location decisions in pop-up retailing for future research. The findings suggest central, high-traffic shopping areas as popular locations for pop-up stores, and indicate the selection of less-obvious and innovative locations as a future trend. Locational decision-making in pop-up retailing is unstructured, centralized, intuitive and low-tech. The decision-making is supported by own experience and networks. Customers, complementary facilities, costs and retail space are identified as essential location factors for pop-up retailers. Adapting promotion and product to the local customer remain an important day-to-day activity for pop-up retailers.